STRATEGIES OF AN EFL TEACHER TO TEACH SPEAKING IN CLASS VIII OF SMPN 2 JOMBANG - Rista Novita Sari; Mukminatus Zuhriyyah (FKIP, Universitas Banten Jaya, 2023)
This research aimed to describe the strategies of teaching speaking in class VIII at one state junior high school in Jombang and find out the EFL teacher’s reasons to use the strategies in class VIII at one state junior high school in Jombang. This research is qualitative research in the form of case study. The data were collected from class observation, documentation, and interview with an EFL teacher and twelve students from three classes of class VIII at one state junior high school in Jombang. The results indicate that the teacher applies several strategies in teaching speaking in class VIII. The teacher applies conversation and direct-practice strategy in teaching asking attention, complimenting/appreciating, and asking and giving opinion, using questioning to check understanding in teaching checking understanding and degrees comparison, presentation in teaching notice material, brainstorming in teaching announcement material, and demonstration strategy in teaching degrees and comparison material. There are several teacher’s reasons in applying the strategies in teaching speaking to improve students’ skill ability.